ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI (STUDI KASUS DI WILAYAH KERJA KANTOR PELAYANAN PAJAK BATU) - Dina W Fitriani; Putu Mahardika Adi Saputra (Journal of Indonesian Applied Economics, 2009)
The objective of this study is mainly to analyze factors that influence the amount ofpersonal  income  tax  that collected by Batu  tax  service office  in  its work areas.  Inorder  to address  the research questions,  this paper utilizes  the multiple regressionanalysis. Shortly, our findings conclude that the most dominant factor that influencesour dependent variable is the amount of registered taxpayers.Keywords: personal income tax, taxpayer, multiple regression analysis